2021
DOI: 10.1007/s11661-021-06544-7
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Al2O3–ZrO2-Based Composites, Formed via CSC Method, in Linear Infrastructure Applications Based on Their Mechanical, Thermal and Environmental performance

Abstract: Ceramic-ceramic composites have been prepared using the centrifugal slip casting method (CSC). The method has so far been mainly utilized in making ceramic-metal composites. Al2O3–ZrO2 composites have been obtained with different shares of ZrO2, i.e., 15, 50 and 75 vol pct, respectively. Prior to sintering the composite samples, the rheological properties of the casting slips were investigated and thermogravimetric tests were performed. Upon sintering, all three series of the ceramic composites showed a densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Based on the histogram, it was found that the actual size of the powders was close to the manufacturer's stated size. Similar conclusions were obtained in previous work [17,28]. The SEM images of the metal powders are shown in Figure 4.…”
Section: Description Of the Raw Powderssupporting
confidence: 90%
“…Based on the histogram, it was found that the actual size of the powders was close to the manufacturer's stated size. Similar conclusions were obtained in previous work [17,28]. The SEM images of the metal powders are shown in Figure 4.…”
Section: Description Of the Raw Powderssupporting
confidence: 90%
“…The observations showed that alumina tends to form agglomerates. Data from the literature [30] show that nanometric powders, which characterize a high surface-areato-single-particle volume ratio, can form agglomerates. Analysis of the obtained histogram shows that the alumina particle size distribution is unimodal (Figure 1).…”
Section: Description Of the Initial Powdersmentioning
confidence: 99%